Activation of the Transducers of Unfolded Protein Response in Plants - Nawkar, Ganesh M.; Lee, Eun Seon; Shelake, Rahul M.; Park, Joung Hun; Ryu, Seoung Woo; Kang, Chang Ho; Lee, Sang Yeol (Frontiers in Plant Science, 2018)
Maintenance of homeostasis of the endoplasmic reticulum (ER) ensures the balance between loading of nascent proteins and their secretion. Certain developmental conditions or environmental stressors affect protein folding causing ER stress. The resultant ER stress is mitigated by upregulating a set of stress-responsive genes in the nucleus modulating the mechanism of the unfolded protein response (UPR). In plants, the UPR is mediated by two major pathways; by the proteolytic processing of bZIP17/28 and by the IRE1-mediated splicing of bZIP60 mRNA. Recent studies have shown the involvement of plant-specific NAC transcription factors in UPR regulation. The molecular mechanisms activating plant-UPR transducers are only recently being unveiled. This review focuses on important structural features involved in the activation of the UPR transducers like bZIP17/28/60, IRE1, BAG7, and NAC017/062/089/103. Also, we discuss the activation of the UPR pathways, including BAG7-bZIP28 and IRE1-bZIP60, in detail, together with the NAC-TFs, which adds a new paradigm to the plant UPR.